Mechanochemical synthesis of hyper-crosslinked polymers: influences on their pore structure and adsorption behaviour for organic vapors - Grätz, Sven; Zink, Sebastian; Kraffczyk, Hanna; Rose, Marcus; Borchardt, Lars (Beilstein Journal of Organic Chemistry, 2019)
This study elucidates a mechanochemical polymerization reaction towards a hyper-crosslinked polymer as an alternative to conventional solvent-based procedures. The swift and solvent-free Friedel–Crafts alkylation reaction yields a porous polymer with surface areas of up to 1720 m2g−1 and pore volumes of up to 1.55 cm3g−1. The application of LAG (liquid-assisted grinding) revealed a profound impact of the liquid´s boiling point on the textural properties of the obtained polymer materials. Finally, the materials are characterized by vapour sorption experiments with benzene and cyclohexane.
Keywords: hyper-crosslinked polymers; mechanochemistry; microporous; solvent-free; vapor sorption

Handbook of Porous Solids - Schüth, F.; Sing, K. S. W.; Weitkamp, J. (Wiley-VCH Verlag GmbH, 2002)

(untitled) - Schneemann, A.; Bon, V.; Schwedler, I.; Senkovska, I.; Kaskel, S.; Fischer, R. A. (Chem. Soc. Rev., 2014)

(untitled) - Ding, S.-Y.; Wang, W. (Chem. Soc. Rev., 2013)

(untitled) - Chaoui, N.; Trunk, M.; Dawson, R.; Schmidt, J.; Thomas, A. (Chem. Soc. Rev., 2017)

(untitled) - Martín, C. F.; Stöckel, E.; Clowes, R.; Adams, D. J.; Cooper, A. I.; Pis, J. J.; Rubiera, F.; Pevida, C. (J. Mater. Chem., 2011)

(untitled) - Li, C.; Liu, M.; Pschirer, N. G.; Baumgarten, M.; Müllen, K. (Chem. Rev., 2010)

(untitled) - Kuhn, P.; Antonietti, M.; Thomas, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Pandey, P.; Katsoulidis, A. P.; Eryazici, I.; Wu, Y.; Kanatzidis, M. G.; Nguyen, S. T. (Chem. Mater., 2010)

(untitled) - Ritter, N.; Senkovska, I.; Kaskel, S.; Weber, J. (Macromol. Rapid Commun., 2011)

(untitled) - Tan, L.; Tan, B. (Chem. Soc. Rev., 2017)

(untitled) - Schute, K.; Rose, M. (ChemSusChem, 2015)

(untitled) - Rightmire, N. R.; Hanusa, T. P. (Dalton Trans., 2016)

(untitled) - Tan, D.; Loots, L.; Friščić, T. (Chem. Commun., 2016)

(untitled) - Xu, C.; De, S.; Balu, A. M.; Ojeda, M.; Luque, R. (Chem. Commun., 2015)

(untitled) - Bolm, C.; Hernández, J. G. (Angew. Chem., Int. Ed., 2019)

(untitled) - Michalchuk, A. A. L.; Tumanov, I. A.; Boldyreva, E. V. (CrystEngComm, 2019)

(untitled) - Tan, D.; García, F. (Chem. Soc. Rev., 2019)

(untitled) - Howard, J. L.; Cao, Q.; Browne, D. L. (Chem. Sci., 2018)

(untitled) - Andersen, J.; Mack, J. (Green Chem., 2018)

(untitled) - Do, J.-L.; Friščić, T. (Synlett, 2017)

(untitled) - Užarević, K.; Wang, T. C.; Moon, S.-Y.; Fidelli, A. M.; Hupp, J. T.; Farha, O. K.; Friščić, T. (Chem. Commun., 2016)

(untitled) - Leistenschneider, D.; Jäckel, N.; Hippauf, F.; Presser, V.; Borchardt, L. (Beilstein J. Org. Chem., 2017)

(untitled) - Schneidermann, C.; Jäckel, N.; Oswald, S.; Giebeler, L.; Presser, V.; Borchardt, L. (ChemSusChem, 2017)

(untitled) - Zhang, E.; Hao, G.-P.; Casco, M. E.; Bon, V.; Grätz, S.; Borchardt, L. (J. Mater. Chem. A, 2018)

(untitled) - Karak, S.; Kandambeth, S.; Biswal, B. P.; Sasmal, H. S.; Kumar, S.; Pachfule, P.; Banerjee, R. (J. Am. Chem. Soc., 2017)

(untitled) - Karadeniz, B.; Howarth, A. J.; Stolar, T.; Islamoglu, T.; Dejanović, I.; Tireli, M.; Wasson, M. C.; Moon, S.-Y.; Farha, O. K.; Friščić, T.; Užarević, K. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Fidelli, A. M.; Karadeniz, B.; Howarth, A. J.; Huskić, I.; Germann, L. S.; Halasz, I.; Etter, M.; Moon, S.-Y.; Dinnebier, R. E.; Stilinović, V.; Farha, O. K.; Friščić, T.; et al. (Chem. Commun., 2018)

(untitled) - Chen, Y.; Wu, H.; Liu, Z.; Sun, X.; Xia, Q.; Li, Z. (Ind. Eng. Chem. Res., 2018)

(untitled) - Casco, M. E.; Badaczewski, F.; Grätz, S.; Tolosa, A.; Presser, V.; Smarsly, B. M.; Borchardt, L. (Carbon, 2018)

(untitled) - Ohn, N.; Shin, J.; Kim, S. S.; Kim, J. G. (ChemSusChem, 2017)

(untitled) - Grätz, S.; Borchardt, L. (RSC Adv., 2016)

(untitled) - Ravnsbæk, J. B.; Swager, T. M. (ACS Macro Lett., 2014)

(untitled) - Malca, M. Y.; Ferko, P.-O.; Friščić, T.; Moores, A. (Beilstein J. Org. Chem., 2017)

(untitled) - Ohn, N.; Kim, J. G. (ACS Macro Lett., 2018)

(untitled) - Grätz, S.; Wolfrum, B.; Borchardt, L. (Green Chem., 2017)

(untitled) - Zhu, X.; Tian, C.; Jin, T.; Browning, K. L.; Sacci, R. L.; Veith, G. M.; Dai, S. (ACS Macro Lett., 2017)

(untitled) - Troschke, E.; Grätz, S.; Lübken, T.; Borchardt, L. (Angew. Chem., 2017)

(untitled) - Jamal, R.; Shao, W.; Xu, F.; Abdiryim, T. (J. Mater. Res., 2013)

(untitled) - Biswal, B. P.; Chaudhari, H. D.; Banerjee, R.; Kharul, U. K. (Chem. – Eur. J., 2016)

(untitled) - Zhu, X.; Hua, Y.; Tian, C.; Abney, C. W.; Zhang, P.; Jin, T.; Liu, G.; Browning, K. L.; Sacci, R. L.; Veith, G. M.; Zhou, H.-C.; Jin, W.; et al. (Angew. Chem., Int. Ed., 2018)

(untitled) - Posudievsky, O. Y.; Kozarenko, O. A. (Polym. Chem., 2011)

(untitled) - Grätz, S.; Oltermann, M.; Troschke, E.; Paasch, S.; Krause, S.; Brunner, E.; Borchardt, L. (J. Mater. Chem. A, 2018)

(untitled) - Rose, M.; Klein, N.; Senkovska, I.; Schrage, C.; Wollmann, P.; Böhlmann, W.; Böhringer, B.; Fichtner, S.; Kaskel, S. (J. Mater. Chem., 2011)

(untitled) - Grätz, S.; Beyer, D.; Tkachova, V.; Hellmann, S.; Berger, R.; Feng, X.; Borchardt, L. (Chem. Commun., 2018)

(untitled) - Andersen, J.; Mack, J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Detoni, C.; Gierlich, C. H.; Rose, M.; Palkovits, R. (ACS Sustainable Chem. Eng., 2014)

(untitled) - Schute, K.; Detoni, C.; Kann, A.; Jung, O.; Palkovits, R.; Rose, M. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Wang, G.; Dou, B.; Wang, J.; Wang, W.; Hao, Z. (RSC Adv., 2013)

(untitled) - de Lange, M. F.; Verouden, K. J. F. M.; Vlugt, T. J. H.; Gascon, J.; Kapteijn, F. (Chem. Rev., 2015)